DOES RECREATIONAL HUNTING OF LYNX REDUCE DEPREDATION LOSSES OF DOMESTIC SHEEP? - HERFINDAL, IVAR; LINNELL, JOHN D. C.; MOA, PÅL F.; ODDEN, JOHN; AUSTMO, LARS B.; ANDERSEN, REIDAR (The Journal of wildlife management, 2005)
Eurasian lynx (Lynx lynx) are responsible for significant depredation on domestic lambs in Norway. Recreational hunting of lynx is widely used to limit lynx population growth and to attempt to remove problem individuals. We analyzed the relationship between annual changes in lamb losses and lynx hunting on 2 scales. On the county scale, lamb losses were related to the size of the lynx population that was reduced through the harvest of 294 lynx by hunters during our study, 1995–2001. At the level of individual grazing areas, we documented a significant local effect of lynx harvest (n = 321 lynx); however, the magnitude of this benefit was so small (13 lambs per male lynx, or 2 lambs per female lynx) as to be of little practical benefit. The data indicate that lynx hunting only reduces depredation when it reduces the size of the population.